2017
DOI: 10.1038/s41467-017-01045-x
|View full text |Cite|
|
Sign up to set email alerts
|

Low frequency transcranial electrical stimulation does not entrain sleep rhythms measured by human intracranial recordings

Abstract: Transcranial electrical stimulation has widespread clinical and research applications, yet its effect on ongoing neural activity in humans is not well established. Previous reports argue that transcranial alternating current stimulation (tACS) can entrain and enhance neural rhythms related to memory, but the evidence from non-invasive recordings has remained inconclusive. Here, we measure endogenous spindle and theta activity intracranially in humans during low-frequency tACS and find no stable entrainment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(168 citation statements)
references
References 79 publications
4
159
4
1
Order By: Relevance
“…As the strength of endogenous rhythm can determine entrainment by tACS (17), NREM sleep with a strongly synchronized slow wave rhythm could be more resilient to tACS than the desynchronized state of REM sleep. This may explain why a recent study could not entrain NREM slow waves even beyond the sham level (18). Counterintuitively, one study reported disruptive effects of tACS on slow wave activity in NREM during an afternoon nap (19) and another study reported physiological changes following tACS during night NREM sleep (6).…”
Section: Resultsmentioning
confidence: 99%
“…As the strength of endogenous rhythm can determine entrainment by tACS (17), NREM sleep with a strongly synchronized slow wave rhythm could be more resilient to tACS than the desynchronized state of REM sleep. This may explain why a recent study could not entrain NREM slow waves even beyond the sham level (18). Counterintuitively, one study reported disruptive effects of tACS on slow wave activity in NREM during an afternoon nap (19) and another study reported physiological changes following tACS during night NREM sleep (6).…”
Section: Resultsmentioning
confidence: 99%
“…That is, tACS at the relatively weak stimulation intensity used here (~1.8 mA peak-to-peak) may be more effective in modulating a pre-existing neural entrainment (induced by a given rhythmic sensory input) than in inducing neural entrainment in the absence of external sensory rhythms. Concurrent recordings of neural activity during transcranial stimulation show that weak-intensity tACS may not induce neural oscillations when neural activity is not strongly rhythmic (Lafon et al 2017), but could affect already present narrow-band neural rhythms (Reato et al 2010). This could explain why low-frequency tACS is most effective at frequencies close to ongoing brain rhythms (Kanai et al 2008), and in sensory stimulus-induced entrainment settings Zoefel, Archer-Boyd, and Davis 2018;Wilsch et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the current that actually reaches neural tissue is relatively weak Opitz et al, 2016). This issue has led to ongoing debates about whether and how tACS can manipulate neural activity (Krause, Vieira, Csorba, Pilly, & Pack, 2019;Lafon et al, 2017;Opitz, Falchier, Linn, Milham, & Schroeder, 2017;Ruhnau, Rufener, Heinze, & Zaehle, 2018;Vöröslakos et al, 2018;Vosskuhl, Strüber, & Herrmann, 2018). Our study addresses two experimental variableselectrode montage and statistical analysiswhich need to be carefully considered in tACS studies of speech processing.…”
Section: Methodological Implicationsmentioning
confidence: 99%